ASSESSMENT OF MICROBIAL LOAD ON HYGIENICALLY SLAUGHTERED PIG CARCASSES - Suresh , P; Malmarugan, S (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A study was carried out to assess the Total Viable Count and E.coli count in both fresh and chilled (24 hrs) pork samples from 15 hygienically slaughtered pig carcasses. The results revealed that 24 hrs chilling mildly reduced the total viable count but there was good reduction in E.coli count.